Peace and Conflict Resolution in Islam: A Perspective Building - Wani, Nazar Ul Islam (Universitas Islam Indonesia, 2023)
The critics of Islam have hypothesized that several teachings of Islam jeopardize the modern nation-state and its law and order. Islam is perceived as a part of the problem rather than a solution. Islam, however, has a rich inheritance of addressing conflicts in the world. The Islamic texts and Muslim heritage approaches to conflict resolution draw on religious values and present a considerable wealth of responses based on positive solutions to the conflict. The terms/concepts like social justice al-adl to the terms like sulh, translated as settlement and mūslāha translated as reconciliation, wasta (patronage-mediation), tāhkim (arbitration), and importantly salam a peace greeting among Muslims form the conceptual framework of the conflict resolution and peacebuilding in Islam. The specific term for non-violence in the Arabic language is not known, however the alternate vocabulary which stresses non-vehemence and peace is al-unf (no force), sabr (patience), akhlāq (virtuous character), etc. Since the conflict begins within a person, one strives to resolve that conflict through aql (intellect) to fight al-hawa (passions and desire) to overcome jahl (ignorance) with ikhlas (purity) then ihsan (beneficence) or putting the good and beautiful into practice is exercised and above all fighting for social justice jihad. This paper is an effort to build the theoretical aspect of Islam and conflict resolution. A descriptive research design has been employed for the present study. The data was collected through primary and secondary sources of information, and the method of data collection adopted was content analysis.